Hubungan antara Kesadaran Orang Tua Tentang Perkembangan Bahasa Dengan Kemampuan Bahasa Ekspresif Pada Anak Usia Prasekolah di KB-TK Aisyiyah Al-Amin Surakarta - Vina Wibowo, Devriani; Gunawan, Gunawan (Jurnal Terapi Wicara dan Bahasa, 2023)
Abstract Background: The development of language skills in children is divided into 2, one of which is expressive language skills. An expansive language ability is a person's ability to convey messages verbally or in writing. The development of children can be influenced due to the awareness of the closest people, especially parents. But in reality, there are still many parents who do not have awareness of their role in stimulating children's language from an early age. Awareness consists of 5 aspects including AWAREness namely, Attention, Wakefulness, Architecture, Recall of Knowledge and Emotive. Purpose: The purpose of this study was to determine the relationship between parents' awareness about language development and expressive language skills in preschool-age children in KB-TK Aisyiyah Al-Amin Surakarta. Methods: This research is a quantitative study using a Cross Sectional research design. The sample used was 30 respondents based on the general benchmark of "role of thumb". The sampling technique uses purposive sampling technique. The statistical test used is the Spearman Rank correlation test. Results: Parents' awareness of language development was in the good category of 15 parents (50.0%). Enough for 10 parents (33.3%), and less for 5 parents (16.7%). Expressive language skills in the above category averaged 12 respondents (40.0%), in the average category there were 13 respondents (43.3%) while the remaining 5 respondents (10.0%) were in the below average category. The results of the bivariate analysis obtained that the p value was 0.001 which indicated that the p value was 0.001 <0.05 and the correlation coefficient (r) was 0.560. Conclusion: Parents' awareness of language development is related to expressive language skills in preschool-age children in Aisyiyah Al-Amin Surakarta Kindergarten with moderate correlation strength. Keywords: Parental awareness, expressive language skills, age preschool.